2014
DOI: 10.1016/b978-0-12-800097-7.00004-x
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Molecular Mechanisms of Mitosis and Cytokinesis in Trypanosomes

Abstract: Trypanosoma brucei, a unicellular eukaryote and the causative agent of human sleeping sickness, possesses multiple single-copy organelles that all need to be duplicated and segregated during cell division. Trypanosomes undergo a closed mitosis in which the mitotic spindle is anchored on the nuclear envelope and connects the kinetochores made of novel protein components. Cytokinesis in trypanosomes is initiated from the anterior tip of the new flagellum attachment zone, and proceeds along the longitudinal axis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 139 publications
(238 reference statements)
0
26
0
Order By: Relevance
“…Trypanosomatids follow a closed type of mitosis where the nuclear envelope does not disrupt during the mitosis (Ogbadoyi et al ., ; Zhou et al ., ) and unlike higher eukaryotes (Hernandez‐Verdun, ), their nucleoli also remain intact throughout the cell division cycle (Boucher et al ., ). To have an insight into the role of nucleolar TWF during cell division, we examined the dividing Leishmania cells using confocal microscopy after their labelling with anti TWF and anti α‐tubulin antibodies.…”
Section: Resultsmentioning
confidence: 99%
“…Trypanosomatids follow a closed type of mitosis where the nuclear envelope does not disrupt during the mitosis (Ogbadoyi et al ., ; Zhou et al ., ) and unlike higher eukaryotes (Hernandez‐Verdun, ), their nucleoli also remain intact throughout the cell division cycle (Boucher et al ., ). To have an insight into the role of nucleolar TWF during cell division, we examined the dividing Leishmania cells using confocal microscopy after their labelling with anti TWF and anti α‐tubulin antibodies.…”
Section: Resultsmentioning
confidence: 99%
“…In the early branching parasitic protozoan Trypanosoma brucei, 11 CDK-related kinases, designated CRK1-CRK4 and CRK6 -CRK12, have been identified (22,23). CRK1 and CRK3 are involved in controlling the G 1 /S transition and the G 2 /M transition, respectively (24 -26).…”
mentioning
confidence: 99%
“…2) indicated that the drug blocked the entry of trypanosomes into the S-phase. The bilobe, a centrincontaining cytoskeletal structure at the base of the flagellum (Esson et al, 2012), is duplicated in S-phase (Zhou et al, 2014). We postulated that because AEE788 prevented S-phase entry (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Division of the kinetoplast precedes mitosis forming a 2K1N population (Woodward and Gull, 1990). Mitosis produces 2K2N trypanosomes, which become two 1K1N cells after cytokinesis (Sherwin and Gull, 1989), completing the division cycle (for review, see Hammarton, 2007;Li, 2012;Zhou et al, 2014).…”
Section: Introductionmentioning
confidence: 99%